Re-orient? MNC penetration and contemporary shifts in the global political economy - Arno Tausch; Almas Heshmati (Institute for the Study of Labor (IZA), 2009)
This article analyses IMF estimates of economic growth in 180 countries (IMF, 2009), and inks the results to the Re-orient approach, put forward by Frank, 1998. With global economic gravitation shifting to the Indian Ocean/Pacific region, the article also analyses the role of MNC (foreign capital) penetration as the key variable of past quantitative dependency studies for contemporary economic growth and social performance. In a Schumpeterian fashion, MNC penetration reflects the power, which transnational oligopolies wield over local economies. Today, social polarization and stagnation increase as a consequence of the development model, based on high MNC penetration.
urn:nbn:de:101:1-20091009948
Keywords: F50; O10; 330; International relations and international political economy; economic development; technological change; growth; Internationale Wirtschaftsbeziehungen; Multinationales Unternehmen; Entwicklung; Geopolitik; Public Choice; Welt; Asien